Hybrid simulation of a structure to tsunami loading. Issue 1 (January 2020) - Forouzan, Bahareh; Baragamage, Dilshan SP Amarsinghe; Shaloudegi, Koushyar; Nakata, Narutoshi; Wu, Weiming
A new hybrid simulation technique has been developed to assess the behavior of a structure under hydrodynamic loading. It integrates the computational fluid dynamics and structural hybrid simulation and couples the fluid loading and structural response at each simulation step. The conventional displacement-based and recently developed force-based hybrid simulation approaches are adopted in the structural analysis. The concept, procedure, and required components of the proposed hybrid simulation are introduced in this article. The proposed hybrid simulation has been numerically and physically tested in case of a coastal building impacted by a tsunami wave. It is demonstrated that the force error in the displacement-based approach is significantly larger than that in the force-based approach. The force-based approach allows for a more realistic and reliable structural assessment under tsunami loading.